Self-supported formation of hierarchical NiCo2O4 tetragonal microtubes with enhanced electrochemical properties. Issue 3 (26th January 2016) - Ma, Fei-Xiang; Yu, Le; Xu, Cheng-Yan; Lou, Xiong Wen (David)
Abstract : Hierarchical NiCo2 O4 tetragonal microtubes prepared by a self-supported chemical transformation process exhibit an excellent electrochemical performance. Abstract : Hierarchical tetragonal microtubes consisting of ultrathin mesoporous NiCo2 O4 nanosheets have been obtained by annealing nickel cobalt layered double hydroxide microtubes which are synthesized by a one-step solvothermal method. Benefiting from the unique structural features, these hierarchical NiCo2 O4 microtubes manifest an excellent electrochemical performance in terms of high specific capacitance and remarkable cycle life as a battery-type electrode for hybrid supercapacitors.